CNVs targeting genes that regulate exposure to toxicants in Autism Spectrum Disorder (ASD): a role for gene-environment interactions - Santos, J.X. (2017)
We thank the main funders of Autism Genome Project (AGP): Autism Speaks (USA), the Health Research Board (Ireland); the Medical Research Council (UK), the Hilibrand Foundation (USA), Genome Canada, the Ontario Genomics Institute, and the Canadian Institutes of Health Research (CIHR) and the Simons Foundation (SFARI 124827) for data access; Santos JX, Asif M and Marques AR are fellows of the PhD program in Biological Systems, Functional & Integrative Genomics (BioSys) and awardees of scholarships funded by Fundação para a Ciência e Tecnologia (FCT); Rasga C is a recipient of a fellowship from the Autism Spectrum Disorders in the European Union (ASDEU) programme, funded by DG-SANCO (SANCO/2014/C2/035).